Taxing Multinational Enterprises Under ‘Unitary Taxation’: Possible Implications for SDGs Implementation Programmes (Dhaka University Law Journal, 2025)
Corporate income tax payable by corporations, particularly the multinational enterprises (MNEs) forms one of the important sources of domestic taxation. Nevertheless, there is allegation of widespread tax avoidance by MNEs through exploiting the gaps and loopholes in the existing taxation system. Regulatory measures are being taken to prevent these tax avoidances, both at the domestic and international levels but no effective outcome is seen yet. In this context of the failure of the present taxation system, different alternative options are emerging, one of which is unitary taxation system. There is consensus among international tax practitioners and scholars that unitary system, if implemented worldwide, could tackle the tax avoidance by MNEs effectively and ensure the fair share of corporate income tax to those countries where the MNEs run their actual business activities. Consequently, it is proposed in this study that if the governments get more tax revenues under unitary taxation system, they can use this money for Sustainable Development Goals (SDGs) implementation programmes as SDGs implementation programmes need huge amount of finance in addition to other courses of action.Dhaka University Law Journal Vol.35, Issue.2, December 2024 P. 105-137